The Effect of ESG on ASEAN Public Companies’ Green Innovation per 2021 - Julius Tzar; Sylvia Veronica Nalurita Purnama Siregar (Indonesian Journal of Economics and Management, 2023)
The aim of this study is to test the effect of ESG on ASEAN public companies’ green innovation per 2021. By doing a directed content analysis combined with the assistance of autocoding through machine learning, evidence shows that ASEAN companies were still slow in terms of adapting several green innovation dimensions. Furthermore, we do an OLS regression analysis that includes several financial control variables to determine the effect of the ESG score on the ASEAN firms’ green innovations. In conjunction with that we also run robustness checks by using robust OLS regression and the result is aligned with the common OLS regression. Finally, this article summarizes that there is a significant effect of the ESG score on ASEAN companies’ green innovation and hopefully the investors can rely on the ESG score to interpret the green innovations done by the companies.